Power systems analysis illustrated with MATLAB and ETAP - Madhusudan, Shertukde Hemchandra (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2018)
'Electrical power is harnessed using several energy sources, including: coal, hydel, nuclear, solar, and wind. Generated power is needed to be transferred over long distances to support load requirements of customers viz: residential, industrial, and commercial. This necessitates proper design and analysis of Power Systems to efficiently control the power flow from one point to the other without delay, disturbance, or interference. Ideal for utility and power system designer professionals and students, this book is richly illustrated with MATLAB and etap (Electrical Transient Analysis Program) to succinctly illustrate concepts throughout, and includes examples, case studies, and problems'--
Includes bibliographical references.
Keywords: MATLAB; Electric power systems -- Design and construction; Electric power systems -- Computer simulation